O hudožestvennoj reči A. P. Čehova. Materialy k slovarû antonimov pisatelâ - Vežbinʹski, Âroslav (Stylistyka, 2002)
The article is based оп the lexical contrasts excerpted from literary works Ьу Chekhov (over 4,000 quotatioпs as the examples of antonymous contrasts). lt attempts at examining the proЫem of antonymous refere11ces in Chekhov’s prose as well as at presentiпg certain amount of examples which will Ье used in the dictionary. The empirical material presented in the article plays essential role in semantics, lexicology, lexicography, expressive stylistics and idiostylistics. The language of literary works Ьу Chekhov broadens lexical contrasts. The analysis shows that the structure ofnumerous antonyms becomes increasingly complex due to the shift of semantic accents, the domination of consta11t elements over the dictionary meanings. Apart from codified oppositions, which in Chekhov prose are subject to пumerous semantic transformatioпs, there are also antonymous realisatioпs that appear as coпtextual opposites. A11to11yms present the writer’s specific mаппеr of speaking and to some extend successfully describe his style.